Marketing Strategy Analysis of Asin Asked MSMEs in The Covid-19 Pandemic Period in Kesenden, Cirebon - Aditya, Oriza (Green Publisher Indonesia, 2020)
The Covid-19 pandemic has changed many aspects of life, one of which is in the economy. This has animpact on economic instability, one of which is the impact of MSMEs, such as the occurrence of abnormalities in the supply of raw materials, consumer interest and marketing. This study aims to describe the marketing strategies that must be carried out by MSME actors so that they can survive and become more responsive to changes when Covid-19 occurs. In this study using qualitative methods with interview techniques in Kesenden, Cirebon. From the results of the research conducted, it can be concluded that the Covid-19 pandemic can provide opportunities and can also provide threats (Treath) to MSMEs, marketing strategies in the midst of the Covid-19 pandemic, namely by improving the quality of products and services, customer relationship marketing, and e-commerce